Growth and reproduction of the slug Deroceras laeve (Muller)(Pulmonata: Stylonmmatophora) under controlled conditions - Faberi, A.J.=700 1 Lopez, A.N.; Manetti, P.L.; Clemente, N.L.; Alvarez Castillo, H.A.
(Es, En)
ilus., 13 ref.
Keywords: BABOSAS; PLAGAS DE PLANTAS; CRECIMIENTO; SUPERVIVENCIA; REPRODUCCION; CICLO DE VIDA; TEMPERATURA; ESPAÑA; DEROCERAS LAEVE; CURVA DE CRECIMIENTO; PARAMETROS BIOLOGICOS